Evaluating systems of soil evaluating systems of soil conservation: results from a bio-economic model - Dumsday, R.G.; Flinn, J.C. (International Institute of Tropical Agriculture, 1975)
Farming systems in the lowland humid tropics as elsewhere, are a consequence of the interaction of complex bio-physical and socio-economic relationships. Further, the time sequence of the flow of inputs, many of which are beyond the control of the farmer, and the flow of output results in the farmer operating in a dynamic, uncertain environment.